MORPHOLOGICAL STATE OF BURN SCARS OF SKIN UNDER THE CONDITIONS OF USING SILICON PLATES - Волков, Р.К.; Білаш, С.М. (World of Medicine and Biology, 2015)
The results of histological studies of skin of burned patients in the stage of formation scar tissue and under the conditions of using silicone plates are represented in this work. Established that imposition of silicone plates on the areas of damaged skin, which are healing reduces the formation of scars, histologically detected the reorganization of the dermis, decreasing of the functional activity of fibroblasts and reducing the formation of bundles of collagen fibers.